2012
DOI: 10.2478/v10290-012-0003-y
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical harvesting of plums for processing with a continuously moving combine harvester

Abstract: Eleven plum cultivars (Prunus domestica L.) for processing grafted on semidwarf rootstock ‘Wangenheim Prune’ and vigorous rootstock ‘Myrobalan’ were densely planted (1000, 1250, 1666, 2500 trees ha-1) and trained to central leader spindle tree. A new training system was applied to obtain trees suitable for mechanical harvesting. The leader was not headed after planting and summer training procedures were performed in May/June. From the third year onwards, renewal pruning was carried out after fruit harvesting.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 7 publications
0
12
0
Order By: Relevance
“…Most of the flowers and fruits in 2010-2015 were growing on 2-year-old shoots and the proportions between 1-, 2-, and 3-year-old shoots were the same for trees growing on all types of plots (Table 4). However, according to Mika et al (2012), on 3-year-old trees of the cultivar Valjevka growing in an herbicide fallow system, the greatest number of fruits grew on 1-year-old shoots, although the differences between the percentages of fruits growing on 1-, 2-, and 3-year-old shoots were not significant. On control, mulched, and mowed plots sprayed with herbicides, fruit setting on 2-year-old shoots was considerably better than on 1-year-old and 3-year-old shoots (Table 4).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the flowers and fruits in 2010-2015 were growing on 2-year-old shoots and the proportions between 1-, 2-, and 3-year-old shoots were the same for trees growing on all types of plots (Table 4). However, according to Mika et al (2012), on 3-year-old trees of the cultivar Valjevka growing in an herbicide fallow system, the greatest number of fruits grew on 1-year-old shoots, although the differences between the percentages of fruits growing on 1-, 2-, and 3-year-old shoots were not significant. On control, mulched, and mowed plots sprayed with herbicides, fruit setting on 2-year-old shoots was considerably better than on 1-year-old and 3-year-old shoots (Table 4).…”
Section: Resultsmentioning
confidence: 99%
“…Production in Poland, consisting mainly of the fruits of Prunus domestica L., is estimated at 100,000 t. The Serbian cultivar Valjevka is characterized by high quality of fruits, tolerance to plum pox virus (Ogašanovic, 1990), midseason time of ripening, low susceptibility to diseases and pests (Głowacka and Rozpara, 2014), and suitability for mechanized harvest with combine harvesters (Mika et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…At present, several species of fruit bushes, sour cherries, olives, plums, and other species are mechanically harvested (Brown et al 1983;Wawrzyńczak et al 1998;Jiménez et al 2011;Ferguson et al 2012;Mika et al 2012). Experimental works are still being conducted to improve harvesting technology (Ampatzidis et al 2012;Larbi & Karkee 2014;He et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Fruits were not suitable for the fresh market because of bruising. Mika et al (2012) demonstrated mechanical harvesting of densely planted plum trees trained to the central leader, and pruned by the renewal method, with a self-propelled straddle canopy contact harvester. The harvesting efficiency was 2-3 t·h -1 , with 90-95% effectiveness.…”
Section: Introductionmentioning
confidence: 99%
“…In European prune-producing regions, prune flowering time is generally from late March to early April (Milosevic et al, 2010;Šebek, 2013). However, frost damage during flowering time may reduce fruiting outcomes (Mika et al, 2012;Neumüller, 2011;Yao, 2011). In Izumo, the flowering time is from late March to mid-April, which is during frost season.…”
Section: Relationship Between Weather Conditions During Flowering Andmentioning
confidence: 99%